1984
DOI: 10.1104/pp.76.1.184
|View full text |Cite
|
Sign up to set email alerts
|

Flavan-3-ol Biosynthesis

Abstract: Extrats of cel sspnin culturs from Douglas fir (Puado wa minzinji) nedls catalyzed the prductio of (+)-catechin (2,3-tran flavan-3-ol) from the 2,-tras-flavan,3,4-cis-diol (leucocyanidin) in a NADPH-dependent redutas reaction at pH 7A. Catechin was also produced, along with the 3,4-ci-didl, in a double step reductio from (+)-dihydroquercetin. It was necessary to eliminate any thibl such as 2-mercaptoethanol or dithiothreitol from the extract or assay mixture becanse these thiols apparently formed thioethers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…The identity of the minor product as (+)-catechin was unequivocally established by co-migration of the radioactivity with an authentic standard in various chromatographic systems (section 2. NADPH-dependent reactions, have also been reported by STAFFORD and co-workers (12,13,14,15) in connection with proanthocyanidin biosynthesis in cell cultures of Douglas fir needies, and by HELLER et al (7) in connection with anthocyanidin biosynthesis in Matthiola incana. Whereas pH-optima of 7.4 and 6.0 were found for the enzymes involved in proanthocyanidin and anthocyanidin biosynthesis, respectively, the (+)-dihydroquercetin reductase activity from barley grains showed pH-optima at both 7.0 and 6.0.…”
Section: Enzymatic Reduction Of (+)-Dihydro-mentioning
confidence: 63%
See 1 more Smart Citation
“…The identity of the minor product as (+)-catechin was unequivocally established by co-migration of the radioactivity with an authentic standard in various chromatographic systems (section 2. NADPH-dependent reactions, have also been reported by STAFFORD and co-workers (12,13,14,15) in connection with proanthocyanidin biosynthesis in cell cultures of Douglas fir needies, and by HELLER et al (7) in connection with anthocyanidin biosynthesis in Matthiola incana. Whereas pH-optima of 7.4 and 6.0 were found for the enzymes involved in proanthocyanidin and anthocyanidin biosynthesis, respectively, the (+)-dihydroquercetin reductase activity from barley grains showed pH-optima at both 7.0 and 6.0.…”
Section: Enzymatic Reduction Of (+)-Dihydro-mentioning
confidence: 63%
“…the leucocyanidin to (+)-catechin have been reported by STAFFORD and co-workers (12,13,15) in extracts of cell cultures of Douglas fir needles.…”
Section: (+)-23-trans-34-cis-leucocyanidin and Thenmentioning
confidence: 99%
“…Several remarkable advances are reported in reviews (12,19,20,36,37). Stafford (20,38,39) revealed that dihydroflavonol 4-reductase and leucoanthocyanidin reductase catalyzed dihydroflavonols to leucoanthocyanidins, then to 2,3-trans-2R,3S-flavan-3-ol (C or GC) and speculated that 2,3-trans-2R,3S-flavan-3-ol was converted to 2,3-cis-2R,3R-flavan-3-ol (EC or EGC) by an epimerase. However, Xie et al (21) reported a new flavan-3-ol biosynthesis pathway in which the anthocyanidin reductase, encoded by the BANYLUS gene in Arabidopsis and Medicago truncatula (21), converted anthocyanidins into their corresponding 2, 3-cis-2R, 3R-flavan-3-ols such as EC, epiafzelechin, and EGC in the presence of NADPH.…”
Section: Galloylation Of Catechins In Teamentioning
confidence: 99%
“…As such it catalyses the last common step in the biosynthesis of the most abundant flavonoids, i.e. flavan-3-ols and condensed tannins [9][10][11][12][13][14][15][16][17][18]. Because of this strategic position, DFRs with distinct substrate specificities may exert an important control on the pattern of anthocyanins and proanthocyanidins which are produced downstream.…”
Section: Introductionmentioning
confidence: 99%